2018
DOI: 10.2340/16501977-2316
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between internal and external handcycle training load in people with spinal cord injury training for the handbikebattle

Abstract: TRIMPsRPE and TRIMPHR showed very large correlations with external training load, and thus appear appropriate for use in monitoring handcycling training load in people with paraplegia. How-ever, it is recommended that both measures are used in combination, when possible, since some individuals showed weaker relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…All participants are screened and train in self-organizing teams of their rehabilitation center for a period of 4-5 months prior to the HBB event. Data from this project showed that self-regulated handcycle training over a period of five months can increase peak power output (þ17%), peak oxygen uptake (þ7%), peak ventilation (þ9%) and reduce fat mass index (À6.3%), BMI (À2%) and waist circumference (À4%) [65,83,113,114].…”
Section: Health Benefitsmentioning
confidence: 98%
“…All participants are screened and train in self-organizing teams of their rehabilitation center for a period of 4-5 months prior to the HBB event. Data from this project showed that self-regulated handcycle training over a period of five months can increase peak power output (þ17%), peak oxygen uptake (þ7%), peak ventilation (þ9%) and reduce fat mass index (À6.3%), BMI (À2%) and waist circumference (À4%) [65,83,113,114].…”
Section: Health Benefitsmentioning
confidence: 98%
“…It would, therefore, be an ideal method to monitor training sessions in rehabilitation. Previous studies showed large to nearly perfect correlations (0.5 À 0.97) among TRIMP sRPE and HR-based TRIMP methods in sprint kayak, wheelchair basketball, soccer, cycling and recreational handcycling [15,[17][18][19][20]. Whereas very large to nearly perfect correlations (0.81 À 0.95) were found between TRIMP sRPE and TSS in cycling and recreational handcycling [19,20].…”
Section: Introductionmentioning
confidence: 94%
“…While the case studies of Abel et al and Zeller et al remain the only work in elite handcyclists, 6,24 de Groot et al did research the training load of ten trained athletes over a 12week period. 48 Athletes reported 5-47 training sessions with a mean intensity of 85 ± 20 W (PO peak : 159 ± 29 W) and 132 b min −1 (HR peak : 178 ± 12 b min −1 ). Furthermore, de Groot et al noted high correlations between external training load, 48 when calculated as a "Training Stress Score," 66 and internal training load using session RPE and HR training impulse methods.…”
Section: Training Monitoringmentioning
confidence: 99%
“…48 Athletes reported 5-47 training sessions with a mean intensity of 85 ± 20 W (PO peak : 159 ± 29 W) and 132 b min −1 (HR peak : 178 ± 12 b min −1 ). Furthermore, de Groot et al noted high correlations between external training load, 48 when calculated as a "Training Stress Score," 66 and internal training load using session RPE and HR training impulse methods. This adds to the work of Goosey-Tolfrey et al who also found RPE to be a valid means for monitoring handcycling training intensity.…”
Section: Training Monitoringmentioning
confidence: 99%